Formulation and Characterization of Proniosomal Gels loaded with Levofloxacin for dermal drug Delivery. - Lina K. Abdel Salam; Mona M. A. Abdelmottaleb; Ahmed S. Geneidi (Ain Shams University, 2022)
The study aim: Formulation of proniosomal gels and evaluation of their potential in dermal drug delivery of levofloxacin, an antibacterial drug used to treat complicated bacterial infections. Methods : Levofloxacin-loaded proniosomal gels were prepared using coacervation phase separation using nonionic surfactants [spans and tweens]. Different parameters of the proniosomal gels were evaluated, including particle size [PS], zeta potential [ZP], drug entrapment efficiency percentage [EE%], in vitro drug release and ex vivo permeation studies. Results: Based on the experimental results, the EE% for the prepared formulas ranged from 32.22±0.86 to 54.83±1.17 %. Comparatively to others, levofloxacin could be best encapsulated using span 20. The particle size of the proniosomes ranged from 447±204 nm to 1089±17 nm. Proniosomal gel prepared wth span 20 had the smallest vesicle size. The zeta potential range of prepared proniosomes was from 20.95±0 mV to 60.92±0.09 mV. The prepared formulations were found to have a polydispersity index ranging from 0.198±3.23 to 0.967±0.36. Almost all of the formulas displayed a linear release profile ranging from 33.028 to 97.56 percent over 4 hours. A higher level of drug deposition was observed with span 80 compared to tween 80 after 6 hours: 18.296 % versus 9.44%. The stability study showed that there was no significant change in EE%, PS, or ZP of levofloxacin proniosomal gels after 3 months of storage. Conclusion: The dermal application of the investigated proniosomal gel formulations demonstrated promising results as nanocarriers for levofloxacin.